Adherence to a Semiannual Surveillance Program for Hepatocellular Carcinoma in Patients With Liver Cirrhosis. Issue 6 (July 2017) - Mancebo, Alejo; González-Diéguez, María Luisa; Navascués, Carmen A.; Cadahía, Valle; Varela, María; Pérez, Ramón; Rodrigo, Luis; Rodríguez, Manuel
Abstract : Background: Patient adherence to screening for hepatocellular carcinoma (HCC) is not well known. Our aims were to analyze the adherence to a surveillance program in a prospective cohort of cirrhotic patients and to examine its association with HCC stage at diagnosis. Materials and Methods: A total of 770 patients with cirrhosis were examined semiannually by ultrasound and alpha-fetoprotein at a tertiary center. We collected data on 17 variables at baseline. Suboptimal adherence was defined as failure to complete 2 consecutive screening rounds. Results: Over a median follow-up period of 42.0 months (interquartile range: 60.0), 125 patients (16.2%) had suboptimal adherence. Active or previous intravenous drug use [hazard ratio (HR), 5.33; 95% confidence interval (CI), 3.07-9.23], active alcohol consumption (HR, 3.03; 95% CI, 2.03-4.51), absence of liver decompensation before the inclusion in the program (HR, 1.65; 95% CI, 1.07-2.55) and aspartate transaminase/alanine transaminase ratio ≥1.6 (HR, 1.82; 95% CI, 1.23-2.70) were independent predictors of suboptimal adherence. Compared with those with optimal adherence, patients with suboptimal adherence had a more advanced HCC stage at diagnosis ( P =0.015), they were less frequently treated with curative intention ( P =0.078) and survived less (median: 14.2 mo; IQR: 36.0 vs. 22.7 mo; IQR: 47.4; P =0.160), although these differences were not significant. Conclusions: The adherence to the process of HCC surveillance can be considered as adequate among cirrhotic patients. Active alcohol consumption and a history of intravenous drug use are the strongest predictors of suboptimal adherence. These patients have a more advanced HCC stage at diagnosis and tend to be less frequently treated with curative intention.